Web-Based Treatment Program Using Intensive Therapeutic Contact for Patients With Eating Disorders: Before-After Study - ter Huurne, Elke D; Postel, Marloes G; de Haan, Hein A; Drossaert, Constance H.C; DeJong, Cor A.J (JMIR Publications, 2013)
BackgroundAlthough eating disorders are common in the Netherlands, only a few patients are treated by mental health care professionals. To reach and treat more patients with eating disorders, Tactus Addiction Treatment developed a web-based treatment program with asynchronous and intensive personalized communication between the patient and the therapist. ObjectiveThis pilot study evaluated the web-based treatment program using intensive therapeutic contact in a population of 165 patients with an eating disorder. MethodsIn a pre-post design with 6-week and 6-month follow-ups, eating disorder psychopathology, body dissatisfaction, Body Mass Index, physical and mental health, and quality of life were measured. The participant's satisfaction with the web-based treatment program was also studied. Attrition data were collected, and participants were classified as noncompleters if they did not complete all 10 assignments of the web-based treatment program. Differences in baseline characteristics between completers and noncompleters were studied, as well as reasons for noncompletion. Furthermore, differences in treatment effectiveness, treatment adherence, and baseline characteristics between participants of the three major eating disorder diagnostic groups EDNOS (n=115), BN purging (n=24), and BN nonpurging (n=24) were measured. ResultsOf the 165 participants who started the web-based treatment program, 89 participants (54%) completed all of the program assignments (completers) and 76 participants (46%) ended the program prematurely (noncompleters). Severe body dissatisfaction and physical and mental health problems seemed to have a negative impact on the completion of the web-based treatment program. Among the participants who completed the treatment program, significant improvements were found in eating disorder psychopathology (F=54.6, df = 68, P<.001, d=1.14). Body dissatisfaction, quality of life, and physical and mental health also significantly improved, and almost all of these positive effects were sustained up to 6 months after the participants had completed the web-based treatment program. Body Mass Index improved only within the group of participants suffering from obesity. The improvement in eating disorder psychopathology occurred in all three eating disorder diagnostic groups, and the percentage of completers did not differ significantly between these groups. Participants' satisfaction with the treatment program, as well as with their therapist, was high, and participants indicated that they would recommend the program to other patients with eating disorders. ConclusionsThe results of this study suggest that the web-based treatment program has the potential to improve eating disorder psychopathology in patients with different types of eating disorders.